Barreiras à intenção de adoção da tecnologia blockchain em cadeias de suprimentos: percepções em países emergentes - Oliveira, Fabiano Cardoso de (Universidade do Vale do Rio dos Sinos, 2022)
Blockchain is an emerging technology with a wide range of possible applications and the potential to revolutionize the supply chain. In its architecture, the attributes of decentralization, encryption (security), consensus mechanism (trust), immutability, etc. thus, in order to investigate the factors which impact the intention of adopting this technology in supply chains, this thesis aimed to analyze the barriers to the intention of adopting Blockchain technology in Supply Chains in the context of emerging markets. For this purpose, a quantitative and qualitative study was chosen, carried out in two stages. In the quantitative stage, a theoretical model was tested, conceived in the thesis, based on structural equation modeling (PLS-SEM). While in the qualitative stage, a study was carried out with a focus group in order to verify how the relationships of the developed model are established. The focus group stage was carried out with 7 experts between Supply Chain (SC) managers and Blockchain project managers. The results achieved in the quantitative stage, from the analysis of 336 complete questionnaires through the modeling of structural equations, showed that three hypotheses of the study are supported and one is rejected. Notably, it was identified that the predictor variables Interorganizational Barriers, Intraorganizational Barriers and Legislation Barriers explain 34.2% of the variance in the dependent variable Intention to Adopt Blockchain Technology in Supply Chains in the context of emerging markets. Regarding the focus group, some evidence corroborated the factors that constitute the barriers analyzed in the quantitative phase of this study. In the analyzed barriers, it is highlighted the fact that the intraorganizational barriers presented the highest value for the path coefficient, indicating that it is the construct with the greatest explanatory power of the dependent variable. In general, it was observed that the lack of trust between the members of an allied supply chain and a fear of sharing the data constitute some of the main factors that form the barriers to the adoption of BC technology in SC according to the participants of the focus group. Regarding the contributions of this thesis, some of the contributions of this work are highlighted below. First, the results suggest that the Intra and Interorganizational factors constitute the main barriers to the adoption of BC technology in SC. In addition, it was identified that some factors that constitute barriers may present differences between developed and emerging markets. Finally, several research paths are presented for future research.
Keywords: Blockchain; Cadeia de suprimentos; Países emergentes; Emerging markets; Supply chain; ACCNPQ::Ciências Sociais Aplicadas::Administração